2014
DOI: 10.1111/are.12624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a dietary administration of purple coneflower (Echinacea purpurea) on growth, antioxidant activities and 8 miRNAs expressions in crucian carp (Carassius auratus)

Abstract: Echinacea purpurea (EP), a globally popular herbal medicine, has been used to treat various diseases in human and animals. However, little has been reported about its effects in fish. In this study, crucian carp (Carassius auratus) were selected to evaluate the effects of EP on growth performance and antioxidant response and the expressions of micro-RNAs. The results showed EP could stimulate the growth of crucian carp with the best effect was observed at dose of 4 g kg À1 . In serum, the content of hydroxyl r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Echinacea purpurea (EP) is a globally popular herbal medicine known as an immunostimulant in humans, animals, and fish [ 46 ]. In fish, dietary supplementation with EP has been reported to enhance the immune response and resistance against bacterial infection [ 47 , 48 , 49 ] and cause a significant increase in serum lysozymes and bactericidal activity (SBA) [ 48 ], thus leading to stimulation of the fish immune system and improvement in health status.…”
Section: Discussionmentioning
confidence: 99%
“…Echinacea purpurea (EP) is a globally popular herbal medicine known as an immunostimulant in humans, animals, and fish [ 46 ]. In fish, dietary supplementation with EP has been reported to enhance the immune response and resistance against bacterial infection [ 47 , 48 , 49 ] and cause a significant increase in serum lysozymes and bactericidal activity (SBA) [ 48 ], thus leading to stimulation of the fish immune system and improvement in health status.…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on the antioxidant function of Echinacea has revealed that the addition of 0.5–2.0% Echinacea into animal feed could increase the Trolox equivalent antioxidant capacity, as well as catalase (CAT) and SOD activity in the serum and spleen of broilers [ 26 ]. Similarly, adding Echinacea into the diet of crucian carp could stimulate their growth performance and elicit an antioxidant response [ 44 ]. Feeding a large yellow croaker with 150 mg/kg of Astragalus polysaccharides increased liver T-AOC, GSH-Px and lysozyme activities [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on the antioxidant function of Echinacea has revealed that the addition of 0.5-2.0% Echinacea to animal feed increased the Trolox equivalent antioxidant capacity, as well as catalase (CAT) and SOD activity, in the serum and spleen of broilers [30]. Similarly, adding Echinacea to the diet of crucian carp stimulated their growth performance and elicited an antioxidant response [45]. Feeding large yellow croaker with 150 mg/kg of Astragalus polysaccharides increased liver T-AOC, GSH-Px, and lysozyme activities [46].…”
Section: Effects Of Plant Polysaccharides Combined With Boric Acid On...mentioning
confidence: 99%